Integration of miRNAs, Degradome, and Transcriptome Omics Uncovers a Complex Regulatory Network and Provides Insights Into Lipid and Fatty Acid Synthesis During Sesame Seed Development - Zhang, Yin-Ping; Zhang, Yuan-Yuan; Thakur, Kiran; Zhang, Fan; Hu, Fei; Zhang, Jian-Guo; Wei, Peng-Cheng; Wei, Zhao-Jun (Frontiers in Plant Science, 2021)
Sesame (Sesamum indicum L.) has always been known as a health-promoting oilseed crop because of its nutrient-rich oil. In recent years, studies have focused on lipid and fatty acid biosynthesis in various plants using high-throughput sequencing. Here, we integrated transcriptomics, small RNAs, and the degradome to establish a comprehensive reserve intensive on key regulatory miRNA targeting circuits to better understand the transcriptional and translational regulation of the oil biosynthesis mechanism in sesame seed development. Deep sequencing was used to differentially express 220 miRNAs, including 65 novel miRNAs, in the different developmental periods of seeds. GO and integrated KEGG analysis revealed 32 pairs of miRNA targets with negatively correlated expression profiles, of which 12 miRNA-target pairs were further confirmed by RT-PCR. In addition, a regulatory co-expression network was constructed based on the differentially expressed gene profiles. The FAD2, LOC10515945, LOC105161564 and LOC105162196 genes were clustered into groups that regulate the accumulation of unsaturated fatty acid (UFA) biosynthesis. Our results provide a unique advanced molecular platform for the study of lipid and fatty acid biosynthesis, and this study may serve as a new theoretical reference to obtain the increased levels of UFA from higher-quality sesame seed cultivars and other plants.